Oral antidiabetes agents for the management of inpatient hyperglycaemia: so far, yet so close. Issue 9 (7th June 2020) - Koufakis, T.; Mustafa, O. G.; Zebekakis, P.; Kotsa, K.
Abstract: Background: Hyperglycaemia is an ongoing challenge in hospital settings and is associated with poor outcomes. Current recommendations for the management of inpatient hyperglycaemia suggest insulin as the main glucose‐lowering treatment choice and limit the administration of oral antidiabetes agents to a small proportion of cases because of safety concerns. Aim: To present and critically appraise the available evidence on the use of oral antidiabetes agents in the hospital setting and the risk–benefit balance of such an approach in the era of cardiovascular outcomes trials. Methods: PubMed, Embase and Google Scholar databases were searched to identify relevant published work. Available evidence on the efficacy and the safety profile of oral agents in the context of their use in hospitalized individuals are summarized and discussed in this narrative review. Results: There is no robust evidence to suggest the use of metformin,  thiazolidinediones, sulfonylureas and sodium‐glucose co‐transporter‐2 inhibitors in the hospital setting, although some of their effects on acute outcomes deserve further evaluation in future studies. However, the use of dipeptidyl peptidase‐4 inhibitors in inpatients with type 2 diabetes is supported by a few, well‐designed, randomized controlled trials. These trials have demonstrated good safety and tolerability profiles, comparable to insulin glucose‐lowering efficacy, and a reduction in insulin dose when dipeptidyl peptidase‐4 inhibitors are co‐administered with insulin, in individuals with mild to moderate hyperglycaemia and a stable clinical condition. Conclusion: The administration of dipeptidyl peptidase‐4 inhibitors to specific groups of inpatients might be a safe and effective alternative to insulin. What's new?: Guidelines for the management of inpatient hyperglycaemia generally recommend against the use of oral agents. There is no robust evidence to suggest the use of metformin,  thiazolidinediones, sulfonylureas and sodium‐glucose co‐transporter‐2 inhibitors in the hospital setting. The administration of dipeptidyl peptidase‐4 inhibitors to inpatients with mild to moderate hyperglycaemia might be a safe and effective alternative to insulin.